Dead zones why earth's waters are losing oxygen - Hand, Carol 1945- (Minneapolis Twenty-First Century Books, 2016)
Times are tough for shrimpers and fishers in the Gulf of Mexico. The animals they rely on for their livelihood are harder to find. Every summer a dead zone--a region of low oxygen--emerges in the waters along the Gulf Coast. Where oxygen is low, fish and others animals cannot survive. Currently the world has more than 400 identified dead zones, up dramatically from the 49 dead zones identified in the 1960's. The good news is that people can eliminate dead zones by changing agricultural practices and reducing pollution. Using real-world examples, this book looks at the impact of pollution on global water resources, and discusses the interconnectedness of ecosystems and organisms. --
Death in the depths -- Oxygen for life -- The corn connection -- A planetary problem -- Success and failure.
Includes bibliographical references (pages 72-77) and index.
1230L
12-18.
Grades 9 to 12.
104933
Keywords: Fish kills -- Juvenile literature; Fishes -- Effect of water pollution on -- Juvenile literature; Anoxic zones -- Juvenile literature; Marine eutrophication -- Juvenile literature; Nutrient pollution of water -- Juvenile literature; Juvenile works